The Institutional and Legal Justification of the Restriction of Freedom of Movement in Conditions of Counteraction the Spread of the Covid-19 Pandemic - R. Krusian, Anzhelika (2020)
The study touches upon the issue of determining the current state of ensuring and restricting freedom of movement in Ukraine in the context of counteracting the spread of the COVID - 19 pandemic. Particular attention is paid to the substantive component and the expediency of certain restrictions on freedom of movement, namely: self-isolation and observation. The normative-legal bases of restriction of the constitutional right to freedom of movement are investigated and gaps of their substantiation are revealed.